Correspondence Analysis of Scholastic Potential and English Literacy Skills of Grade XII Students of Islamic-based Schools in Palopo City - Uleng, Budiarti Putri; Nugraha, Yuda Satria (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study aims to determine the relationship between scholastic potential and English literacy skills of grade XII students of Islamic-based schools in Palopo City. This research is based on the phenomenon of the low graduation rate of students from Islamic-based schools compared to public schools in the selection process for entering state universities. This is an ex post facto research. The research population was all grade XII students of Islamic-based schools in Palopo City. Based on the proportionated stratified random sampling technique, a sample of 206 students was taken from five schools, namely MAN Palopo, SMA Datuk Sulaiman, SMAIT Wahdah Islamiyah, SMA Muhammadiyah, and SMAIT Insan Madani. Data collection was done by giving tests. The data analysis techniques used were descriptive analysis and correspondence analysis. Based on the results of the analysis, scholastic potential and English literacy skills of grade XII students of Islamic-based schools in Palopo City are still low. Scholastic potential has a significant relationship with English literacy skills. Students who have good scholastic potential also have good or even excellent English literacy skills. Students with excellent scholastic potential tend to have English literacy skills at a sufficient level. Meanwhile, students whose scholastic potential is in the sufficient and poor categories also tend to have poor English literacy skills. Therefore, intensive assistance is needed in order to improve students' capabilities in facing university entrance examinations, especially in the scholastic potential and English literacy subtests.